Cost-Effectiveness of the Prenatal Detection of Congenital Heart Diseases: A Systematic Literature Review - Darío Londoño Trujillo; Paula A. Castro García; Kristian K. Rojas López; Karen J. Moreno-Medina; María T. Dominguez Torres; Rodolfo J. Dennis Verano; Nestor F. Sandoval Reyes (Journal of Health Economics and Outcomes Research)
**Background:** Congenital heart disease is the most common congenital condition worldwide, with a prevalence of 80 cases per 10 000 live births. In addition to perinatal morbidity and mortality, it entails long-term consequences such as multiple surgeries, prolonged hospitalizations, lifelong cardiac follow-up, reduced quality of life, risk of heart failure, and premature mortality in adulthood. This significant health and economic burden on healthcare systems and families highlights the relevance of evaluating the cost-effectiveness of methods for early detection of this condition. **Objective:** To conduct a systematic literature review (SLR) to identify and analyze existing economic evaluations on prenatal detection of congenital heart diseases through ultrasound, focusing on the reported cost-effectiveness results and the methodological quality of the evaluated studies according to established criteria. **Methods:** An SLR of economic evaluations was conducted following PRISMA guidelines. A quantitative synthesis of key methodological components of each economic evaluation was performed. The incremental medical costs, effectiveness measures, and cost-effectiveness ratios reported in each study were compiled and compared. The methodological quality was assessed according to compliance with the 24 CHEERS criteria. **Results:** We found 785 articles, of which only 7 met all inclusion criteria. Most were cost-effectiveness analyses, with the most common outcome being number of cases detected. Screening with only 4-chamber views interpreted by general practitioners or cardiologists were dominant strategies compared with screening with 4-chamber plus outflow views interpreted by a general practitioner. Fetal echocardiography was most effective but most expensive. Screening with 4-chamber and outflow view, followed by referral to a specialist, were recommended as the least expensive strategy per defect detected. On average, articles met 17 of the 24 CHEERS criteria. **Discussion:** While recent cost-effectiveness analyses demonstrated improved methodological quality, there was a lack of homogeneity due to differences in comparators and population subgroups analyzed. Despite this heterogeneity, fetal ultrasonography screening was consistently identified as a cost-effective strategy, with its cost-effectiveness heavily influenced by the expertise of the interpreting physician. **Conclusion:** Most studies recommend implementing obstetric ultrasonography screening, without routine fetal echocardiography, for detecting congenital heart diseases.